Refugees in the media: Exploring a vicious cycle of frustrated psychological needs, selective exposure, and hostile intergroup attitudes. (17th May 2019) - Lueders, Adrian; Prentice, Mike; Jonas, Eva
Abstract: Two research objectives underlay the present research. First, we tested how frustrated psychological needs caused by the refugee‐influx influence the endorsement and selection of refugee‐relevant information. Second, we tested how information selection processes contribute to the development of exclusionary attitudes that counteract the integration of refugees into host countries. In a laboratory study ( n = 181), frustrated psychological needs decreased participants' endorsement of a refugee‐friendly essay (vs. a control essay). Additionally, frustrated needs led to a biased selection of refugee‐hostile over refugee‐friendly information and such selection biases, in turn, predicted higher levels of ingroup defense and prejudice toward refugees. The findings imply that host societies' receptiveness to refugees is influenced by the maintenance of basic psychological needs.